Finanzielle Bildung in Deutschland: Eine explorative Analyse - Johannes Treu; Valerie Elss (IU Internationale Hochschule, 2024)
Financial literacy is playing an increasingly important role in today's complex world. Since the beginning of the new millennium, more countries and international organizations have recognized the importance of measuring and educating people about financial literacy, for example, to guide their market behavior. Using the OECD understanding of financial education and with the help of the OECD toolkit for this, the current state of financial literacy was recorded as part of a Germany-wide representative survey. Methodologically, the aim is to use exploratory data analysis to present an initial analysis and evaluation of the primary data collected. This is also linked to an investigation into whether differences can be found regarding financial literacy, whether correlations exist between the various variables, and which factors can explain financial literacy in Germany.
Keywords: G5; G53; 650; Finanzielle Bildung; Financial Literacy; Explorative Datenanalyse